Study on Dispersion of Impulse Discharge in SF6 and Eco-Friendly Insulating Gas C4F7N/CO2 - Tianran Zhang; Fang He; Lubin Chang; Wenjun Zhou (Energies)
In recent years, C4F7N/CO2 gas has been widely studied as an eco-friendly alternative to SF6, which is commonly used in electrical equipment. To ensure electrical equipment reliability, the dispersion of impulse discharge voltage of insulated gas is generally required to be less than 3%. However, experimental results indicate that under fault conditions, such as sudden pressure changes or electric field distortion, the discharge dispersion of both C4F7N/CO2 and SF6 often exceeds 3%. This paper investigates the impact of pressure and electric field nonuniformity on the dispersion of impulse discharge voltage for conventional and eco-friendly insulating gases under varying degrees of electric field nonuniformity. Experiments reveal that under identical conditions, the 9%C4F7N/91%CO2 mixture exhibits lower impulse discharge voltage dispersion compared with SF6. As pressure increases, the dispersion decreases for both gases. Conversely, dispersion increases with higher electric field nonuniformity, and the 9%C4F7N/91%CO2 mixture demonstrates greater sensitivity to electric field nonuniformity than SF6. In practical applications, electrical equipment typically operates under slightly nonuniform electric fields and high pressure, meeting dispersion requirements. However, if electric field distortion causes the nonuniformity factor (f) to exceed 2.4 or if pressure drops below 0.3 MPa then dispersion increases significantly, reducing the reliability of insulation performance data.